PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI (Survei pada karyawan PT. TASPEN (Persero) Kantor Cabang Surakarta) - Tabita Tyasyarani; Suprayitno Suprayitno; Lamidi Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
PT. TASPEN (Persero) Surakarta Branch Office is a State-Owned Enterprise engaged in services in serving participants of Civil Servants and the State Civil Apparatus who manage welfare or old-age social security for employees and their families. PT. Taspen (Persero) Surakarta branch office is committed to improving the performance of the Surakarta branch office to become a superior branch office. The purpose of this study is to (1) analyze the significance of the influence of organizational culture on organizational commitment, (2) analyze the significance of the influence of organizational culture and organizational commitment on employee performance, and (3) analyze whether organizational commitment mediates organizational culture on employee performance.This type of research is a survey of employees of PT. TASPEN (Persero) Surakarta branch office. The type of data uses quantitative and qualitative data. Data sources use primary and secondary data. The research population is all employees of PT. TASPEN (Persero) Surakarta branch office, amounting to 33 employees. The sample of this study was 33 people using the census method. The data analysis techniques using multiple linear test, t test, F test, direct influence test, indirect effect test, path analysis and coefficient of determination. The results show that organizational culture has a significant effect on organizational commitment, organizational culture and organizational commitment have a significant effect on employee performance, and organizational commitment mediates organizational culture on employee performance.